Pembagian Harta Bersama Akibat Perceraian menurut Hukum Islam Kajian terhadap Putusan Pengadilan Agama Yogyakarta Nomor 0297/Pdt.G/2017/PA - Azhari, Moch Azam (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2024)
All creatures of God, including humans, pets, and other animals and plants, are encompassed by the universal divine law of marriage. This is the way that Allah has chosen for His creatures to reproduce and sustain their lives. The issue of property between each husband and wife is one of the consequences of marriage law. Article 35 of the Marriage Law regulates joint property. Marital property is also acquired as joint property. The Compilation of Islamic Law states in Article 1 letter (f) that "Marital property is property acquired separately or jointly by husband and wife during the marriage bond, and in this case, it is called joint property, regardless of whether it is registered in someone's name." In this research method, the researcher will use a qualitative method located at the Yogyakarta Religious Court, and the techniques used to collect data include interviews and documentation. In this study, the researcher will examine the decisions of the Yogyakarta Religious Court related to joint property, where 40% is for the former husband and 60% for the former wife, using the perspective of Islamic law and the Compilation of Islamic law. because Islamic Sharia stipulates that joint property is divided into two for separating couples. Unlike Islamic law, which does not specify how much of the couple's property should be distributed after divorce, half is given to the former wife. Considering that 83 percent of the Indonesian population is Muslim, it is important to look at issues related to the division of joint property decided by the judges of the Yogyakarta Religious Court.